Exploring the experiences and perceptions of haemodialysis patients observing Ramadan fasting: a qualitative study - Adanan, Nurul Iman Hafizah; Wan Md Adnan, Wan Ahmad Hafiz; Khosla, Pramod; Karupaiah, Tilakavati; Mat Daud, Zulfitri 'Azuan (BioMed Central, 2021)
Background: The festival of Ramadan is a month of spiritual reflection for Muslims worldwide. During Ramadan, Muslims are required to refrain from eating and drinking during daylight hours. Although exempted from fasting, many patients undergoing maintenance haemodialysis (HD) opt to participate in this religious practice. Many studies have explored the effects of Ramadan on health outcomes, however, the exploration from patients’ own point of view pertaining to this religious practice is lacking. Thus, we aimed to explore the experiences and perceptions of Muslim HD patients observing Ramadan fasting from three HD centres in Klang Valley, Malaysia. Method: An exploratory phenomenology qualitative study was conducted whereby subjects were purposively selected based on previous experience in observing Ramadan fasting. Face-to-face in-depth interviews were conducted, and study data were analyzed thematically and iteratively coded using a constant comparison method. Results: Four major themes emerged from the data, namely: (i) “fasting experiences”, (ii) “perceived side effects of fasting”, (iii) “health-seeking behavior” and, (iv) “education and awareness needs”. Patients expressed the significance of Ramadan fasting as well as the perceived impact of fasting on their health. Additionally, there is lack of healthseeking behaviour observed among patients thus, raising needs for awareness and education related to Ramadan fasting. Conclusions: Findings of this study shed light on patients’ experiences and perceptions regarding Ramadan fasting which warrants the needs for an effective communication between patients and health care practitioners through a structured-Ramadan specific education program.